Literature Review: Factors Associated with Exclusive Breastfeeding - Tyas Ningrum Rahmadayanti; Nia Kania; Silvia Kristanti Tri Febriana; Triawanti Triawanti; Fujiati Fujiati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Exclusive breastfeeding coverage in Indonesia is also not yet optimal, due to a decline from 68.6% in 2023 to 66.4% in 2024. Infant health risks increase when exclusive breastfeeding practices are not achieved. This study aims to identify factors associated with exclusive breastfeeding, particularly those related to perceived barriers, perceived vulnerability, perceived benefits, spousal support, and maternal employment. A literature review used the PEO (Population, Exposure, Outcome) framework. The literature reviewed was selected based on keywords related to exclusive breastfeeding behavior: perceived vulnerability, perceived benefits, perceived barriers, husband's support, and maternal occupation. Articles published between 2021 and 2025 were selected. The databases used were PubMed and Google Scholar, with 1,074 results. The selection process resulted in 15 articles that met the quantitative criteria, were published between 2021 and 2025, and examined variables relevant to the focus. Two articles noted the relationship between perceived barriers and exclusive breastfeeding, while two other articles noted the link with perceived vulnerability and exclusive breastfeeding. Four articles pointed to the relationship between perceived benefits and exclusive breastfeeding, and four articles highlighted spousal support as a factor. Five articles pointed to the relationship between maternal employment and exclusive breastfeeding. Four articles noted a relationship between spousal support and exclusive breastfeeding. Five articles noted a relationship between maternal employment and exclusive breastfeeding. Perceptions of barriers, perceptions of vulnerability, perceptions of benefits, spousal support, and maternal employment were associated with exclusive breastfeeding practices in most articles.